Community Pharmacy as a Health Empowerment Hub: An X-Banner Education Programme to Strengthen Knowledge and Awareness of Acute Respiratory Infections among Pharmacy Customers in Kalibagor District - Alvin Ulinnuha; Diah Nur Qoniah; Intan Wiji Setyaningsih; Nur Azizah; Fauziah (Indonesian Community Empowerment Journal, 2026)
Acute respiratory infection (ARI) remains a major public-health burden in Indonesia, with the 2023 Indonesian Health Survey reporting a national prevalence of 34.2% and Central Java Province contributing approximately 13.0% of national cases. Community-empowerment programmes that strengthen health literacy at trusted primary contact points such as community pharmacies are aligned with sustainable development goal (SDG) 3 on good health and well-being and with Goals 4, 10, and 17. We designed and evaluated an X-banner-based community-empowerment programme co-created with pharmacy staff and five community representatives at Hazkia Pharmacy, Kalibagor District, Banyumas Regency, in January 2026. We enrolled 100 customers using random sampling from a sequential customer list (Slovin formula). The empowerment medium was a 160 × 60 cm X-banner displaying ARI causes, transmission, symptoms, prevention, and clean and healthy living behaviour (PHBS); customers were exposed passively during routine waiting time of 8–22 minutes. A validated and reliable knowledge-and-awareness questionnaire (piloted in 30 separate respondents; Cronbach's α = 0.84 knowledge, 0.81 awareness) measured outcomes immediately before and after exposure. Wilcoxon signed-rank tests analysed paired changes after non-normality (p = 0.000) and non-homogeneity (p = 0.000) were confirmed. The good-knowledge proportion rose from 27.0% to 99.0% and good-awareness from 29.0% to 100.0%; both improvements were statistically significant (Wilcoxon p < 0.001; rank-biserial r ≈ 0.99). The programme advances SDG 3.3, 3.D, 4.7, 10.3, and 17.17 indicators, embeds a low-cost sustainability action, and offers a replicable model for community-pharmacy-anchored empowerment in Central Java Province.